2019
DOI: 10.3390/su11072186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Regulations on Technological Innovation Efficiency in China’s Industrial Enterprises: A Spatial Analysis

Abstract: China’s traditional industrial model is characterized by high energy consumption and high pollution, which results in many environmental problems that cannot be ignored. To achieve sustainable development, the Chinese government has proposed five development concepts of “innovation, coordination, green, openness, and sharing”. This initiative highlights the urgency of China’s efforts to strengthen environmental regulation. Based on the panel data of industrial enterprises in China from 2006 to 2015, this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 47 publications
1
45
0
Order By: Relevance
“…However, only practical measures or approaches can be implemented. Moreover, according to relevant studies, voluntary regulations positively affect the innovation efficiency of SMEs, while mandatory supervision has no significant effect [36]. The policy composition under the NIS framework involves little supervision and is more focused on the environment and the development of services.…”
Section: Topics Of Policy Textsmentioning
confidence: 99%
“…However, only practical measures or approaches can be implemented. Moreover, according to relevant studies, voluntary regulations positively affect the innovation efficiency of SMEs, while mandatory supervision has no significant effect [36]. The policy composition under the NIS framework involves little supervision and is more focused on the environment and the development of services.…”
Section: Topics Of Policy Textsmentioning
confidence: 99%
“…Currently, although there are many studies discussing the impact of entrepreneurs' innovation activities, those studies mainly focused on description of industrial status and other influencing factors, including regional agglomeration, education and economic development, etc., rather than policy evaluation [16,17]. By analyzing the impact of industrial policies on research and development (R&D) investors, Pack and Saggi [4] and Clausen [18] put forward that the specificity of the policy, the design of incentive mechanism and the follow-up supervision would affect the implementation results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…But, in the long run, the implementation of environmental policies would achieve the win-win goal in terms of enterprises' competitiveness and environmental protection. Zhu et al [32] based their research on the panel data of industrial enterprises in China from 2006 to 2015 to investigate the spatial features of technological innovation efficiency and examine the relationship between technology innovation efficiency and environmental regulations from a spatial perspective. The results indicated that voluntary regulation positively affected the technological innovation efficiency of industrial enterprises at the provincial level, while mandatory regulation had no significant impact.…”
Section: Environmental Regulation and Technical Innovationmentioning
confidence: 99%